Pengaruh Penerapan Sistem Pengendalian Internal, Penggunaan Teknologi Informasi dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Pelaporan Keuangan pada Pemerintah Provinsi Aceh - Saifa Mijra Cofa; Yusliana Yusliana; Fitri Yunina (AKUNTANSI 45, 2025)
This study aims to analyze the effect of the implementation of internal control systems, the use of information technology, and human resource competencies on the quality of financial reporting in the Aceh Provincial Government. Hypothesis testing was conducted using multiple linear regression methods, which include simultaneous and partial tests to determine the effect of independent variables on the dependent variable, both as a whole and individually, at a significance level of 5% (α = 0.05). The sample of this study consisted of 92 employees in the Aceh Provincial Government. The results of the analysis indicate that both simultaneously and partially, the three independent variables, namely the implementation of internal control systems, the use of information technology, and human resource competencies, have a significant influence on the quality of financial reporting in the Aceh Provincial Government. This study provides important insights for local government financial management, particularly in efforts to improve the quality of financial reporting through improvements in control systems, the use of technology, and the development of human resource competencies.